Identification of the Needs of Shipmasters and Shipping Stakeholders Towards Ship Safety Score for Shipping Safety Based on Logistic Regression Model - Prasetyo, Eko; Sumantri, Siswo Hadi; Anwar, Syaiful; Widodo, Pujo (JUKI : Jurnal Komputer dan Informatika, 2023)
An essential component of Indonesia's marine industry is shipping safety. This research aims to determine how important a vessel's safety score is as a potential indicator for reducing the probability of maritime accidents. To determine the meteorological variables that significantly impact ship accidents, we created a logistic regression model using survey data obtained from skippers of vessels operating within Indonesia. Furthermore, the study's findings demonstrate the critical need for objective assessment standards to raise shipping safety. This study offers important new information on creating and implementing thorough safety score criteria for Indonesian sailing license issuance.